Analysis of piston slap motion - Narayan, S. (Zielona Góra: Uniwersytet Zielonogórski)
Piston slap is the major force contibuting towards noise levels in combustion engines. This type of noise depends upon a number of factors such as the piston-liner gap, type of lubricant used, number of piston pins as well as geometry of the piston. In this work the lateral and rotary motion of the piston in the gap between the cylinder liner and piston has been analyzed. A model that can predict the forces and response of the engine block due to slap has been dicussed. The parameters such as mass, spring and damping constant have been predicted using a vibrational mobility model.
Keywords: piston slap; noise; engine acoustics